MANAGEMENT OF INDIRECT COSTS – MATHEMATICAL METHODS FOR COST ALLOCATION - S. Deevski (Trakia Journal of Sciences)
The purpose of this paper is to look into the challenges of management of indirect costs in business organizations and to propose solutions to those problems. The paper starts with an introduction to the importance of understanding the concept of overhead costs and why it is often crucial for the management of the business organizations to classify, analyze and manage them. Particular problems to the allocation of indirect costs arise when supporting departments provide mutual services to each other. In these situation the management has two options – to ignore the mutual provision of services and account for the overheads as if there were no such services or to use simple cost allocation methods. This approach might not lead to reliable information required for taking sound management decision. With the advancement of technologies, the problem of obtaining timely and reliable information about the cost structure of cost objects (products, services, departments, etc.) could be resolved in an effective and efficient way using a third option. Namely, the utilization of mathematical methods for indirect cost allocation. The author performed a survey among managers of business organizations exploring whether they would use this approach and the results turned out to be positive.